High-surface-area activated red mud for efficient removal of methylene blue from wastewater - Zhong-Pan Hu; Ze-Min Gao; Xinying Liu; Zhong-Yong Yuan (Adsorption Science & Technology)
Red mud was activated by a digestion–precipitation method, resulting in a mesostructure with high surface area, and the activated red mud was further used as the adsorbent for methylene blue removal. The physicochemical properties of the resultant samples were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, thermogravimetry analysis, and nitrogen sorption techniques. Batch studies were measured to investigate the influence factors including adsorbent dosage, contact time, pH, and initial concentration. It was revealed that the activated red mud was highly efficient for removal of methylene blue. Adsorption experiments were found to be better achieved in faintly acidic and alkaline conditions, where the adsorption capacity of activated red mud and activated red mud-200 reached 232 and 274 mg/g at pH 7.0, respectively. Langmuir, Freundlich, Temkin isotherms, and pseudo-second-order kinetic model fitted the experimental data well, demonstrating an electrostatic interaction mechanism.